Study on the Miscibility of Polypyrrole and Polyaniline Polymer Blends - Tekalign A. Tikish; Ashok Kumar; Jung Yong Kim (Advances in Materials Science and Engineering)
We report on the miscibility and phase behaviour of polypyrrole-polyaniline (PPy/PANI) as a function of blend composition. The PPy/PANI blends were prepared by solution processing method, using dimethyl sulfoxide (DMSO) solvent. Characterization of the polymer blends was carried out based on the data analysis from Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and differential scanning calorimetry (DSC). The PPy/PANI system was successfully formed blends in DMSO solvent. The polymer blends showed almost amorphous nature in XRD spectra because of intermolecular interaction between PPy and PANI macromolecules, which was confirmed by FT-IR data. Specifically, the DSC result for the PPY : PANI = 50 : 50 wt.% blend showed only one glass transition temperature (Tg), which indicates that the two polymers are well miscible without undergoing any phase separation.